Development of intraxylary phloem and internal cambium in Ipomoea hederifolia (Convolvulaceae) - Patil, Vidya S.; Rao, K. S.; Rajput, Kishore S. [UNESP] (Torrey Botanical Soc, 2009)
V. S. PATIL (Department of Botany, Faculty of Science, The Maharaja Sayajirao University of Baroda, Vadodara-390002 India), K. S. RAO (BRD School of Bioscieces, S. P. University, Vallabh Vidyanagar, India), and K. S. RAJPUT (Department of Botany, Faculty of Science, The Maharaja Sayajirao University of Baroda, Vadodara-390002 India). Development of intraxylary phloem and internal cambium in Ipomoea hederifolia (Convolvulaceae). J. Torrey Bot. Soc. 136: 423-432. 2009-In Ipomoea hederifolia L. (Convolvulaceae), internal/intraxylary phloem originated as isolated strands from the procambially derived cells after the formation of protoxylem and protophloem. Bands of internal phloem were apparent in the sixth internode after the development of metacambium. In the relatively thick stems several small arcs/segments of internal cambium ensues from the parenchyma cells between the protoxylem and internal protophloem. Though all the segments were active, some of them (two of them located opposite to each other) were relatively more active. Bidirectional differentiation of these segments gave rise to secondary xylem centrifugally and secondary phloem centripetally, resulting inverted vascular bundles. Rest of the internal cambium segments were unidirectional and formed only secondary phloem centripetally. Like external vascular cambium, the internal cambium was non-storied. Structurally, secondary xylem and phloem was composed of axial and radial system in which rays were mostly uni- to biseriate. Secondary xylem produced by the internal cambium was more or less similar to the xylem formed by the external successive cambia. Secondary phloem produced by the internal cambium was composed of sieve tubes, companion cells, axial and ray parenchyma cells. Simple sieve plates of internal phloem were mostly arranged on transverse end walls in contrast to compound and obliquely placed sieve plates of external phloem formed by the successive cambia.
Keywords: internal cambium; internal phloem; intraxylary phloem; Ipomoea hederifolia